The $n^{th}$ term of a sequence is $2n-3$, find its $15^{th}$ term.
Answer
Verified
482.4k+ views
Hint: This question can be done by easily understanding the concepts of arithmetic progression which are mentioned below: -
$n^{th}$ term of an A.P (arithmetic progression) is given by ${T_n} = a + (n - 1)d$ where a= first term of the sequence and d=common difference which is given by $d = {T_n} - {T_{n - 1}}$. As already they have given $T_n$ of the sequence, we will just substitute the value of ‘n’ to get the required answer.
Complete step-by-step answer:
Here in this question $n^{th}$ term of a sequence is directly given i.e. (2n-3) so we can directly use this $n^{th}$ term and can find $15^{th}$ term
$ \Rightarrow {T_n} = 2n - 3$ .............equation (1)
Now we have to find the $15^{th}$ term so we will put n=15 in equation 1 to find the $15^{th}$ term.
$ \Rightarrow {T_{15}} = 2(15) - 3$
$ \Rightarrow {T_{15}} = 30 - 3$
$\therefore {T_{15}} = 27$
Therefore the $15^{th}$ term of the sequence will be 27.
Additional Information: In mathematics there are three types of progressions:-
*Arithmetic progression
*Geometric progression
*Harmonic progression
Definition of arithmetic progression: - An arithmetic sequence or progression is defined as a sequence in which for every pair of consecutive terms the second number is obtained by adding a fixed number to the first one. Difference between two consecutive terms is always a constant term.
Note: Alternate method: - We can also solve this question by using formula ${T_n} = 2n - 3$
Now we will find ${T_1}$ term by putting n=1
$ \Rightarrow {T_1} = 2(1) - 3 = - 1$
$\therefore {T_1} = - 1$
Now we will find ${T_2}$ term by putting n=2
$ \Rightarrow {T_2} = 2(2) - 3 = 1$
$\therefore {T_2} = 1$
So, common difference can be find out using formula $d = {T_n} - {T_{n - 1}}$
$ \Rightarrow d = {T_2} - {T_1}$
$ \Rightarrow d = 1 - ( - 1)$ (Putting the values)
$\therefore d = 2$
Therefore common difference is 2
Now we will find $15^{th}$ term by applying formula ${T_n} = a + (n - 1)d$
$ \Rightarrow {T_{15}} = - 1 + (15 - 1)2$ (Putting values of a=1, n=15, d=2)
$ \Rightarrow {T_{15}} = - 1 + (14)2$
$ \Rightarrow {T_{15}} = - 1 + 28$
$\therefore {T_{15}} = 27$
$n^{th}$ term of an A.P (arithmetic progression) is given by ${T_n} = a + (n - 1)d$ where a= first term of the sequence and d=common difference which is given by $d = {T_n} - {T_{n - 1}}$. As already they have given $T_n$ of the sequence, we will just substitute the value of ‘n’ to get the required answer.
Complete step-by-step answer:
Here in this question $n^{th}$ term of a sequence is directly given i.e. (2n-3) so we can directly use this $n^{th}$ term and can find $15^{th}$ term
$ \Rightarrow {T_n} = 2n - 3$ .............equation (1)
Now we have to find the $15^{th}$ term so we will put n=15 in equation 1 to find the $15^{th}$ term.
$ \Rightarrow {T_{15}} = 2(15) - 3$
$ \Rightarrow {T_{15}} = 30 - 3$
$\therefore {T_{15}} = 27$
Therefore the $15^{th}$ term of the sequence will be 27.
Additional Information: In mathematics there are three types of progressions:-
*Arithmetic progression
*Geometric progression
*Harmonic progression
Definition of arithmetic progression: - An arithmetic sequence or progression is defined as a sequence in which for every pair of consecutive terms the second number is obtained by adding a fixed number to the first one. Difference between two consecutive terms is always a constant term.
Note: Alternate method: - We can also solve this question by using formula ${T_n} = 2n - 3$
Now we will find ${T_1}$ term by putting n=1
$ \Rightarrow {T_1} = 2(1) - 3 = - 1$
$\therefore {T_1} = - 1$
Now we will find ${T_2}$ term by putting n=2
$ \Rightarrow {T_2} = 2(2) - 3 = 1$
$\therefore {T_2} = 1$
So, common difference can be find out using formula $d = {T_n} - {T_{n - 1}}$
$ \Rightarrow d = {T_2} - {T_1}$
$ \Rightarrow d = 1 - ( - 1)$ (Putting the values)
$\therefore d = 2$
Therefore common difference is 2
Now we will find $15^{th}$ term by applying formula ${T_n} = a + (n - 1)d$
$ \Rightarrow {T_{15}} = - 1 + (15 - 1)2$ (Putting values of a=1, n=15, d=2)
$ \Rightarrow {T_{15}} = - 1 + (14)2$
$ \Rightarrow {T_{15}} = - 1 + 28$
$\therefore {T_{15}} = 27$
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
10 examples of friction in our daily life
The correct order of melting point of 14th group elements class 11 chemistry CBSE
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE